Broadband near-infrared emitting from Li1.6Zn1.6Sn2.8O8:Cr3+ phosphor by two-site occupation and Al3+ cationic regulation. (July 2020) - Lai, Jun'an; Zhou, Junhe; Long, Zhangwen; Qiu, Jianbei; Zhou, Dacheng; Yang, Yong; Zhang, Ke; Shen, Weihui; Wang, Qi
Abstract: Broadband sources of near-infrared (NIR) radiation have garnered considerable attention in medical applications and non-destructive analysis. In this work, we have synthesized a lithium zinc stannate phosphor Li1.6 Zn1.6 Sn2.8 O8 :Cr 3+ (LZSO:Cr) for broadband NIR light sources. The LZSO:Cr phosphor exhibited broadband excitation band matches exceptionally well with the emission of commercial 450-nm blue light-emitting diode (LED) chips. As expected, the broadband emission of infrared radiation from 650 nm to 1200 nm was realized due to the unique crystal field environment, where Cr 3+ ions were substituted in two distorted octahedral sites. The broad emission spectrum exhibited peaks around 830 nm and 930 nm with a full width at half maximum (FWHM) of ~190 nm and internal quantum efficiency of 53%. The FWHM could be tuned to ~220 nm by co-doping with Al 3+ ions because of the crystal splitting. The luminescence properties including excitation, emission, decay time, and their relationship between the lattice crystal properties have also been investigated. A phosphor-converted LED (pc-LED) was packaged by combining the phosphor with a 450-nm blue LED chip, which proves the feasibility of our design strategy for broadband NIR light sources. Graphical abstract: Unlabelled Image Highlights: A novel broadband near infrared emitting Li1.6 Zn1.6 Sn2.8 O8 :Cr 3+ phosphor was designed and synthesized. Broadband near infrared emitting was from Cr 3+ ions in two distorted octahedral sites. The full width at half-maximum increased from about 190 nm to 220 nm by cationic regulation of Al 3+ ions. The phosphor was packaged into broadband near infrared emitting light source.